Originally Posted by
Swlabr Note that $\displaystyle \phi: G \rightarrow G, g \mapsto g^n$ is a homomorphism and so $\displaystyle (gh)^n = g^{n}h^n$. Also, as it is onto every $\displaystyle h' \in G$ can be written in this form, $\displaystyle h' = h^n$ for some $\displaystyle h \in G$.
Thus, it is sufficient to prove that $\displaystyle g^{n-1}h^n = h^{n}g^{n-1}$.
Now, note that $\displaystyle g^{n}h^{n} = (gh)^n = g(hg)^{n-1}h $
$\displaystyle \Rightarrow g^{n-1}h^{n-1} = (hg)^{n-1} = \underbrace{(hg)(hg)...(hg)}_{n-1} = (hg)^{n}g^{-1}h^{-1} = h^{n}g^{n}g^{-1}h^{-1}$.
Thus, $\displaystyle g^{n-1}h^n = (hg)^{n-1}h = h^{n}g^{n}g^{-1}h^{-1}h = h^{n}g^{n-1}$ as required.
I hope that's correct - haven't had a chance to check it properly as my wife is badgering me to go through and eat lunch!